TEACHING METHODS OF FOREIGN LANGUAGES AT NURSERY SCHOOLS (Web of Teachers: Inderscience Research, 2024)
The article deals with foreign language acquisition of young children before going to a typical primary school. Nevertheless, in this article can be found certain opinions, concepts and proposals about how to provide English language at lite stage children, and also by focusing on some rescarches that were contributed to the area of my investigation might be effective and fruitful to some extend educators.